Persepsi Masyarakat Kota Kudus Dalam Mengkonsumsi Makanan Halal - Siti Humaidatul Ulfa (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2023)
Abstrak The definition of food in terms can be interpreted as everything that can be consumed, both of land and sea origin. Halal food is food that is allowed in Islamic law to consume it. In accordance with the explanation of the Qur'an and the Hadith of Prophet Muhammad SAW. 1). How important is the issuance of halal certificates on food products consumed by the Kudus community? 2). What do scholars think about the factors that cause the people of the Kudus City to continue to consume food that has a halal label? The discussion uses qualitative methods that begin with collecting general theories and arguments, as well as observations, interviews with the public, then religious experts in the city of Kudus. The importance of halal certification issued by BPJPH based on the results of audits and MUI fatwas to provide a sense of security to the Indonesian people, especially in the holy city. The opinion of scholars about the phenomenon that occurs in the Kudus City is still ignorant of the halal label on food. Because the population of the Kudus City is majority Muslim, the process of making and serving it uses Islamic rules for that it does not matter if there is no halal label on the food packaging. Keywords: Islamic Law, Halal, Halal Certification